Different Reactivity of Raw Starch from Diverse Potato Genotypes - Vadim Khlestkin; Ilia Eltsov (Molecules, 2021)
Potato starch is one of the most important renewable sources for industrial manufacturing of organic compounds. Currently, it is produced from mixed potato varieties that often are harvested from different fields. Meanwhile, tuber starches of various potato breeds differ in their crystallinity, granule morphology, and other physical and chemical parameters. We studied the reactions of raw potato starches of different origins to chemical and biochemical reactions typically used for industrial starch modification. The results clearly demonstrate that there is a significant difference in the reactivity of the starches of different potato genotypes. While the main products of the transformations are the same, their preparative yields differ significantly. Thus, tuber starch of certain potato varieties may be more suitable for specific industrial purposes. Starch reactivity may potentially be a phenotypical trait for potato breeding to obtain potato starches for various industrial applications.